Combining ability studies of high-temperature stress tolerant attributes of advance lines of spring wheat under a hot and dry climate of Bhakkar - Parveen, Zubeda; Irshad, Muhammad; Hussain, Khalid; Abbas, Muneer; Hussain, Niaz; Ghaffar, Abdul; Khaliq, Mudassar; Aslam, Muhammad; Ahsan, Shahar Yar (Journal of Pure and Applied Agriculture, 2023)
An expected increase in world temperature requires us to better know the scope of heat stress experienced by plants. So, we highlighted the combining ability of wheat plant to combine successfully with another wheat plant, resulting desirable traits in next generation and it also provides information about the controlling of genetic mechanisms of quantitative traits that helps in the selection of suitable parents under a hot and dry climate. Combining ability analysis was used to get progenies with desirable traits under agro ecological zone of Thal. These analyses were applied to 21 (direct crosses) hexaploid spring bread wheat F1 populations according to 7×7 diallel fashion biometrical approach under three heat stress regimes at Arid Zone Research Institute, Bhakkar, Pakistan during 2018-19 to 2020-21, i.e., TWS12464, TWS1335-1, TWS11510, TWS15105, TWS1578, TWS12245, Gold-16. Spring bread wheat is also known as spring wheat that is planted in spring and harvested in late summer. Results indicated that the mean squares of most traits proved highly significant due to the general combining ability (GCA) and specific combining ability (SCA). The variance ratios of GCA/SCA revealed all of the traits were predominantly under additive genetic control. TWS12464 was the best combiner with a maximum mean performance of all the traits in all temperature stresses followed by the parent namely Gold-16. Moreover, crosses TWS12464 × Gold-16 and TWS1335-1× TWS12464 were the best F1 hybrids. These crosses depicted good positive effects of SCA along with maximum mean performance for dry biomass per plant at anthesis, spikelets per spike, spike length, grain yield per plant in three test environments. These outperforming strains could be used to develop high-yielding temperature stress-resilient wheat cultivars to mitigate the grain yield gap in country terminal heat-prone ecological zone.